2017
DOI: 10.4055/cios.2017.9.3.303
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Continuous Femoral Nerve Block and Adductor Canal Block after Primary Total Knee Arthroplasty

Abstract: BackgroundThis study aimed to compare the effects of femoral nerve block and adductor canal block on postoperative pain, quadriceps strength, and walking ability after primary total knee arthroplasty.MethodsBetween November 2014 and February 2015, 60 patients underwent primary total knee arthroplasty. Thirty patients received femoral nerve block and the other 30 received adductor canal block for postoperative pain control. Before spinal anesthesia, the patients received nerve block via a catheter (20 mL 0.75% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 17 publications
0
31
0
1
Order By: Relevance
“…The adductor canal is located in the middle one‐third of the thigh and runs from the apex of the femoral triangle proximally to the adductor hiatus distally. ACB could block the saphenous nerve, which is the largest sensory branch of the femoral nerve to the knee, while spare the major motor branches of the femoral nerve.…”
Section: Postoperative Analgesic Regimensmentioning
confidence: 99%
See 2 more Smart Citations
“…The adductor canal is located in the middle one‐third of the thigh and runs from the apex of the femoral triangle proximally to the adductor hiatus distally. ACB could block the saphenous nerve, which is the largest sensory branch of the femoral nerve to the knee, while spare the major motor branches of the femoral nerve.…”
Section: Postoperative Analgesic Regimensmentioning
confidence: 99%
“…ACB could block the saphenous nerve, which is the largest sensory branch of the femoral nerve to the knee, while spare the major motor branches of the femoral nerve. Therefore, ACB could provide postoperative pain relief as effectively as FNB without impairment of quadriceps muscle strength, and it is becoming increasingly popular. Except for better quadriceps muscle power, patients with ACB have better early rehabilitation, longer ambulation distance, and shorter length of hospital stay compared with FNB.…”
Section: Postoperative Analgesic Regimensmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of block technique on postoperative strength of the quadriceps muscle has also been previously assessed, and the efficacy of the AC block for preservation of quadriceps strength is well documented in the literature. Seo et al utilized manual muscle testing (MMT) to directly evaluate quadriceps strength, and results demonstrated significantly greater strength among patients receiving AC block compared to patients receiving FN block [12]. Kim et al demonstrated similar findings, and also directly assessed quadriceps strength using a dynamometer [4].…”
Section: Discussionmentioning
confidence: 98%
“…Prospective randomized controlled trials by Shah et al and Kim et al demonstrated no statistically significant difference in reported postoperative pain scores between the two groups [4,11]. Similarly, a retrospective study by Seo et al compared numeric rating scale (NRS) pain scores between groups postoperatively and found that overall, no significant difference existed between the two analgesic techniques for pain relief in TKA [12]. Of note, transient occurrences of significantly greater pain scores among the FN group compared to the AC group were found at rest on PODs 1, 2, and 3, and with the knee at 45 degrees of flexion on days 1 and 2, which were inconsistent with our findings.…”
Section: Discussionmentioning
confidence: 99%